Use of statins after liver transplantation is associated with improved survival: results of a nationwide study. Issue 7 (18th August 2022) - Becchetti, Chiara; Dirchwolf, Melisa; Schropp, Jonas; Magini, Giulia; Müllhaupt, Beat; Immer, Franz; Dufour, Jean‐François; Banz, Vanessa; Berzigotti, Annalisa; Bosch, Jaume; ,
Summary: Background: There is limited information on the effects of statins on the outcomes of liver transplantation (LT), regarding either their use by LT recipients or donors. Aim: To analyse the association between statin exposure and recipient and graft survival. Methods: We included adult LT recipients with deceased donors in a nationwide prospective database study. Using a multistate modelling approach, we examined the effect of statins on the transition hazard between LT, biliary and vascular complications and death, allowing for recurring events. The observation time was 3 years. Results: We included 998 (696 male, 70%, mean age 54.46 ± 11.14 years) LT recipients. 14% of donors and 19% of recipients were exposed to statins during the study period. During follow‐up, 141 patients died; there were 40 re‐LT and 363 complications, with 66 patients having two or more complications. Treatment with statins in the recipient was modelled as a concurrent covariate and associated with lower mortality after LT (HR = 0.35; 95% CI 0.12–0.98; p = 0.047), as well as a significant reduction of re‐LT ( p = 0.004). However, it was not associated with lower incidence of complications (HR = 1.25; 95% CI = 0.85–1.83; p = 0.266). Moreover, in patients developing complications, statin use was significantly associated with decreased mortality (HR = 0.10; 95% CI = 0.01–0.81; p = 0.030), and reduced recurrence of complications (HR = 0.43; 95% CI = 0.20–0.93; p = 0.032). Conclusions: Statin use by LT recipients may confer a survival advantage. Statin administration should be encouraged in LT recipients when clinically indicated. Abstract : Statin use after liver transplantation is associated with improved survival.